Crow Deaths Caused by West Nile Virus during Winter - Dawson, Jennifer R. (Centers for Disease Control and Prevention, 2007)
In New York, an epizootic of American crow (Corvus brachyrhynchos) deaths from West Nile virus (WNV) infection occurred during winter 2004–2005, a cold season when mosquitoes are not active. Detection of WNV in feces collected at the roost suggests lateral transmission through contact or fecal contamination.